2018
DOI: 10.1177/0885328218790313
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic properties of in situ gels composed of hydrophobically modified biopolymers

Abstract: Hemorrhaging often occurs during cardiac surgery, and postoperative bleeding is associated with medical complications or even death. Medical complications resulting from hemorrhaging can lead to longer hospital stays, thus increasing costs. Hemostatic agents are the main treatment for bleeding. In the present study, hemostatic agents composed of aldehyde groups and hydrophobically modified with hyaluronic acid (ald-hm-HyA) and hydrophobically modified gelatin (hm-ApGltn) were developed and their hemostatic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The blood coagulation evaluation was also performed according to a previously reported method. , After mixing 1 mL of α-CD/2.5C9-PVA IC with 1 mL of porcine whole blood containing sodium citrate, blood coagulation was rapidly observed (Figure a, above photo). In contrast, no coagulation was observed when α-CD/PVA was mixed with porcine whole blood (Figure a, below photo).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood coagulation evaluation was also performed according to a previously reported method. , After mixing 1 mL of α-CD/2.5C9-PVA IC with 1 mL of porcine whole blood containing sodium citrate, blood coagulation was rapidly observed (Figure a, above photo). In contrast, no coagulation was observed when α-CD/PVA was mixed with porcine whole blood (Figure a, below photo).…”
Section: Resultsmentioning
confidence: 99%
“…The blood coagulation evaluation was performed via a previously reported method. , Briefly, 1 mL of porcine whole blood, containing sodium citrate (109 mM), and 1 mL α-CD/C9-PVA IC were mixed and vortex stirred for 2 s. The rheological properties of the blood mixtures were evaluated using a rheometer. The storage and loss moduli were obtained using frequency-dependent measurements (angular frequency, 1–100 rad/s; strain, 5%), with the shear modulus determined from the storage modulus result at a frequency of 10 rad/s.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Another modification of a gelatin-based hemostatic for cardiac surgery, ald-hm-HyA/hm-ApGltn, was carried out by R. Mizuta and T. Taguchi. 101 It was synthesized via the Schiff base reaction between aldehyde-hydrophobically modified-hyaluronic acid (ald-hm-HyA) and hydrophobically modified gelatin (hm-ApGltn), and further crosslinked through hydrophobic interactions between the aliphatic chains. Hyaluronic acid (HyA), an important component of the cardiac extracellular matrix, can promote cell adhesion and proliferation by interacting with the HA receptors on erythrocytes.…”
Section: Currently Developed Hemostatic Materials For Coagulopathymentioning
confidence: 99%
“…Topical hemostatic agents are useful for treating wounds in organs and tissues where other hemostatic methods including suture ligation, direct pressure, and electrocautery are not applicable. Currently, a variety of hemostatic agents including gelatin sponges, chitosan dressings, sugar-based hemostats, , and synthetic polymers have been widely employed, and advanced biomaterial designs have been proposed. , Hemostatic agents work based on several mechanisms such as simple blood absorption, sealing defects by chemical cross-linking, physical molecular aggregation, ,, and the use of blood coagulation factors including fibrinogen and thrombin . On the other hand, conventional hemostats often fail to cover wound areas under wet conditions because of poor tissue adhesiveness and do not possess the required properties of a hemostatic wound dressing.…”
Section: Introductionmentioning
confidence: 99%
“…For the design of tissue-adhesive and hemostatic biomaterials, we focused on hydrophobic interaction. We reported that the molecular modification of gelatin with hydrophobic moieties improved the tissue adhesiveness of hydrogels under wet conditions with extracellular matrix (ECM) components. Moreover, the hydrophobic moieties were anchored to blood cells, resulting in improved hemostatic property . Based on this strategy, a wound dressing of tissue-adhesive microparticles (MPs) composed of hydrophobically modified (hm-) gelatin was developed to promote tissue regeneration after surgical treatment. , The hydrophobized MPs (hMPs) swelled with exudates and formed hydrogel films on tissue surfaces through hydrophobic interactions to protect wounds and promote wound healing after ESD.…”
Section: Introductionmentioning
confidence: 99%